Building brand authenticity 7 habits of iconic brands - Beverland, Michael (Palgrave Macmillan, 2009)
"The projection of authenticity is one of the key pillars of marketing. Research reveals that consumers seek authenticity through the brands they choose. This book proposes to do so. Based on extensive research with consumers and brand managers this book offers seven guiding principles for building brand authenticity"--Provided by publisher.